2016
DOI: 10.1186/s13071-016-1617-z
|View full text |Cite
|
Sign up to set email alerts
|

Anti-parasitic activity of pelleted sainfoin (Onobrychis viciifolia) against Ostertagia ostertagi and Cooperia oncophora in calves

Abstract: BackgroundIncreasing anthelmintic-resistance in nematodes of ruminants emphasises the need for sustainable parasite control. Condensed tannin-containing legume forages such as sainfoin (Onobrychis viciifolia) have shown promising anthelmintic properties in small ruminants but this has never been explored in cattle. Therefore, our aim was to examine the efficacy of sainfoin against cattle nematodes in vivo.MethodsFifteen Jersey male calves (2–4 month-old) were allocated into two groups and fed isoproteic and is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 49 publications
4
41
1
1
Order By: Relevance
“…However, despite these apparent losses, sericea lespedeza and sainfoin silage extracts and silages still exerted anthelmintic effects in vitro by inhibiting the exsheathment of H. contortus L3 larvae and in vivo by lowering adult worm burden and fecal egg counts (Heckendorn et al, 2006;Manolaraki, 2011;Terrill et al, 2016). A high activity against O. ostertagi nematodes of the abomasum contrasted with no activity against intestinal Cooperia oncophora nematodes and was associated with 2.3% CTs (g 100 g −1 dry matter by thiolysis) in the abomasum vs. 0.02% CTs in the intestine (Desrues et al, , 2016b(Desrues et al, , 2017. A high activity against O. ostertagi nematodes of the abomasum contrasted with no activity against intestinal Cooperia oncophora nematodes and was associated with 2.3% CTs (g 100 g −1 dry matter by thiolysis) in the abomasum vs. 0.02% CTs in the intestine (Desrues et al, , 2016b(Desrues et al, , 2017.…”
Section: Effects Of Fermentation On Condensed Tannin Activitymentioning
confidence: 90%
See 1 more Smart Citation
“…However, despite these apparent losses, sericea lespedeza and sainfoin silage extracts and silages still exerted anthelmintic effects in vitro by inhibiting the exsheathment of H. contortus L3 larvae and in vivo by lowering adult worm burden and fecal egg counts (Heckendorn et al, 2006;Manolaraki, 2011;Terrill et al, 2016). A high activity against O. ostertagi nematodes of the abomasum contrasted with no activity against intestinal Cooperia oncophora nematodes and was associated with 2.3% CTs (g 100 g −1 dry matter by thiolysis) in the abomasum vs. 0.02% CTs in the intestine (Desrues et al, , 2016b(Desrues et al, , 2017. A high activity against O. ostertagi nematodes of the abomasum contrasted with no activity against intestinal Cooperia oncophora nematodes and was associated with 2.3% CTs (g 100 g −1 dry matter by thiolysis) in the abomasum vs. 0.02% CTs in the intestine (Desrues et al, , 2016b(Desrues et al, , 2017.…”
Section: Effects Of Fermentation On Condensed Tannin Activitymentioning
confidence: 90%
“…This may either be due to sufficient quantities of undegraded CTs or hydrolysis of anthelmintic flavonoids from inactive glycosides (Manolaraki, 2011), or to proteinbound CTs surviving ruminal fermentation and exerting anthelmintic activity in the abomasum, where a lower pH facilitates dissociation of the CT-protein complex ( Jones and Mangan, 1977). A high activity against O. ostertagi nematodes of the abomasum contrasted with no activity against intestinal Cooperia oncophora nematodes and was associated with 2.3% CTs (g 100 g −1 dry matter by thiolysis) in the abomasum vs. 0.02% CTs in the intestine (Desrues et al, , 2016b(Desrues et al, , 2017. However, both nematode species were affected by CTs in the in vitro larval feeding inhibition assay .…”
Section: Effects Of Fermentation On Condensed Tannin Activitymentioning
confidence: 99%
“…Bioactive dietary components such as polyphenols have received a great deal of interest in recent times for their apparent ability to reduce infection and/or egg shedding of pathogenic parasites such as Haemonchus contortus and Ostertagia ostertagi [ 11 , 34 ], as well as enhancing immune function [ 35 ]. In our current study, we found that whilst establishment of A .…”
Section: Discussionmentioning
confidence: 99%
“…The most common flavan-3-ol monomeric subunits are either catechin and its cis -isomer epicatechin, which give rise to procyanidin-type PAC, and gallocatechin and epigallocatechin, which give rise to prodelphinidin-type PAC [ 8 ] ( S1 Fig ). Antimicrobial effects of polyphenols are well-known; PAC- or ellagitannin-containing diets have been shown to effectively reduce helminth infection in sheep, goats, and cattle [ 9 11 ], and PAC-rich supplements have also shown promise in controlling gut pathogens in pigs such as Escherichia coli [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Condensed tannins, also called proanthocyanidins (PAC), have received the most study. Several PAC-containing forages, such as sericea lespedeza ( Lespedeza cuneata ) (Lange et al, 2006; Shaik et al, 2006; Terrill et al, 2009; Acharya et al, 2015), birdsfoot trefoil ( Lotus corniculatus ) (Heckendorn et al, 2007), sainfoin ( Onobrychis viciifolia ) (Heckendorn et al, 2007; Desrues et al, 2016), and sulla ( Hedysarum coronarium ) (Niezen et al, 1998) have been found to show activity against GIN. In vitro testing, using plant derived PAC organic extracts (extraction performed using organic solvents; i.e.…”
Section: Introductionmentioning
confidence: 99%